1999
DOI: 10.1038/sj.ejcn.1600733
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, double-blind trial of chitosan for body weight reduction

Abstract: Background: Overweight and obesity is a prevalent and costly threat to public health. Compelling evidence links overweight and obesity with serious disorders such as cardiovascular diseases and diabetes. Dietary regimen are notoriously burdened with poor compliance. Chitosan is promoted in the US and other countries as an oral remedy to reduce fat absorption and has now been incorporated as a major constituent into several overthe-counter remedies. The primary aim of this study is to investigate the clinical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
96
2
7

Year Published

2002
2002
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(108 citation statements)
references
References 15 publications
3
96
2
7
Order By: Relevance
“…The second line of evidence comes from two recent trials where chitosan use without energy restriction for 4 or 8 weeks failed to increase weight loss over placebo. 21,22 The final, and most conclusive, line of evidence comes from the data reported here: chitosan did not increase fecal fat excretion and thus failed to act via its proposed mechanism. We did not test multiple chitosan products, but we do conclude that the central claim associated with this particular chitosan supplement, fat malabsorption, is false and the associated claims for weight loss are therefore misleading.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The second line of evidence comes from two recent trials where chitosan use without energy restriction for 4 or 8 weeks failed to increase weight loss over placebo. 21,22 The final, and most conclusive, line of evidence comes from the data reported here: chitosan did not increase fecal fat excretion and thus failed to act via its proposed mechanism. We did not test multiple chitosan products, but we do conclude that the central claim associated with this particular chitosan supplement, fat malabsorption, is false and the associated claims for weight loss are therefore misleading.…”
Section: Discussionmentioning
confidence: 55%
“…In two more recent studies, chitosan was used at 2 g=day for 4 weeks or 2.4 g=day for 8 weeks without dietary energy reduction and no effects on body weight were observed. 21,22 In advertising materials for chitosan, it is claimed that it can prevent the absorption dietary fat, up to 120 g per day with this particular product, and can thus be used as a weight control aid for individuals maintaining a high fat diet. 4 There are three lines of evidence that contradict this claim.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in rats also demonstrated the cholesterol-reducing activity of dietary chitosan (Sugano et al, 1980;Gallaher et al, 2000). However, a double-blind, randomized, placebo-controlled clinical study did not find significant differences in body mass index, serum cholesterol or triglycerides in subjects receiving chitosan for four weeks, compared to those receiving placebo (Pittler et al, 1999). In contrast, other authors reported that chitosan significantly lowered serum LDL cholesterol after 8 weeks of treatment (Wuolijoki et al, 1999).…”
Section: Introductionmentioning
confidence: 77%
“…Chitosan, a deacetylated derivative of chitin that is found in the exoskeleton of shrimp and crabs, is a unique, indigestible, nonplant fiber that may aid weight loss by reducing fat absorption in the intestinal tract. Whether chitosan can cause weight loss is inconclusive, as results vary from no effects 55 on body weight loss to mild 27 or moderate effects. [45][46][47] The unique positive charge of chitosan allows it to bind to negatively charged lipids and form a chitosan-fat gel 4-to 5-fold its original weight, causing the lipids to be trapped and excreted.…”
Section: Treatment Groupmentioning
confidence: 99%